Assessment of Competitive Advantages of the Pavlodar Region and its Economic Strength - BAYANDIN, Marat Asilbekovitsh; NARYNBAYEVA, Aina Serikovna; ARYNOVA, Zulfiya Amangeldinovna; BAYANDINA, Gulmira Duisenbayevna; ALIMKHANOVA, Roza Kenzheevna (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
Findings of the analysis of the key competitive advantages of the Pavlodar region, which is a large industrial center of the Republic of Kazakhstan and has substantial economic strength, have been reflected in this article. Competitive advantages of the region, including a rich natural resources potential, availability of a developed industrial and social infrastructure, high scientific and technical capacity, and the connecting role between Central Asia and Siberia, have been reviewed. Solid competitive advantages for investing in the development of the region have been revealed. The authors have stated general positive factors that contribute to expansion of the economic strength of the Pavlodar region and positively influence the sustainability of the development of the regional economy. The problems that influence the competitiveness of the region and reduce the efficiency of using its economic strength have been identified. The opportunities and areas for development of the region in the medium and long term, taking into consideration the indicated development trends, have been summarized.